2015
DOI: 10.1007/s11136-015-1023-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of non-severe hypoglycemic events and treatment in adults: development of the Treatment-Related Impact Measure—Non-severe Hypoglycemic Events (TRIM-HYPO)

Abstract: Study findings demonstrate that the final, 33-item TRIM-HYPO is reliable and valid and may be useful for assessing impacts related to NSHEs in research and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
(46 reference statements)
1
10
0
Order By: Relevance
“…Hypoglycemia impacts emotional health, self-management, daily functioning and life quality. Hypoglycemia burden predicts care needs, clinical and quality of life outcomes [ 69 , 70 , 99 ] Confidence in ability to manage diabetes Confidence in being able to self-manage diabetes is a key goal Self-efficacy predicts support needs, self-management, clinical and quality of life outcomes and complements clinical and behavioral data [ 133 , 134 ] Confidence in access to person-centred diabetes care and support Feeling secure and confident in having quality medical care, relevant technologies and self-management support available is a key goal [ 42 , 135 ] …”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia impacts emotional health, self-management, daily functioning and life quality. Hypoglycemia burden predicts care needs, clinical and quality of life outcomes [ 69 , 70 , 99 ] Confidence in ability to manage diabetes Confidence in being able to self-manage diabetes is a key goal Self-efficacy predicts support needs, self-management, clinical and quality of life outcomes and complements clinical and behavioral data [ 133 , 134 ] Confidence in access to person-centred diabetes care and support Feeling secure and confident in having quality medical care, relevant technologies and self-management support available is a key goal [ 42 , 135 ] …”
Section: Discussionmentioning
confidence: 99%
“…Nonsevere hypoglycemic events (NSHEs), self-treated hypoglycemia (18), may be experienced by 24-85% of patients with diabetes, particularly among insulin users (18)(19)(20). Each patient in the DIAMOND trial was required to wear a blinded CGM device to record glucose concentration (invisible to the patients) for 2 weeks before randomization and for a week before the 12-and 24-week visits.…”
Section: Nonsevere Hypoglycemic Eventsmentioning
confidence: 99%
“…The cost of a NSHE episode used in the study was $20.32, including $11.09 in direct medical costs and $9.23 in indirect costs (35,36). Lowering NSHEs not only reduces the risk of subsequent severe hypoglycemia (37) but also improves QoL, including psychological well-being, adherence to treatment regimens, work productivity, and quality and quantity of sleep (6,18,19).…”
Section: Psamentioning
confidence: 99%
“… 21 Items are rated on a 7-point scale (from 1= very positive impact to 7= very negative impact ) or participants can select ‘not applicable’ (N/A). All seven items and the 7-point scale were retained in the HIP12, and five items were added, based on qualitative research 12 13 and consultation with the PAC, to assess the impact of hypoglycemia on the following domains of life: sleep, sex life, independence, ability to be spontaneous, and ability to keep fit/be active. Composite scores are calculated by averaging the scores across applicable items, with scores <4 indicating a positive impact, a score of 4 no impact, and a score of >4 a negative impact of hypoglycemia on QoL.…”
Section: Methodsmentioning
confidence: 99%
“…Recent qualitative studies show that hypoglycemia impacts an individual’s QoL in many domains, such as relationships, work or studies, sleep, leisure, and physical activities. 12 13 Person-reported outcome measures (PROMs) can be used to quantify the extent of these impacts. However, recent systematic reviews of the quantified impact of hypoglycemia on QoL among adults with T1D or T2D showed substantial heterogeneity in methods used to assess both hypoglycemia and QoL outcomes.…”
Section: Introductionmentioning
confidence: 99%